Scientific Writing Series: Systematic Review - Quispe, Antonio M. (2021)
Introduction: The systematic review is the comprehensive, reproducible, critical, and detailed evaluation of the best available evidence in response to a specific research question. To achieve this, systematic reviews should cover at least the following seven steps: i) a detailed and structured research question using the PICO technique; ii) evidence eligibility criteria; iii) a precise and reproducible search strategy; iv) selection of evidence and data extraction; v) analysis of biases; vi) synthesis of results; and vii) publication. If the data are sufficient and homogeneous, it is feasible to include their meta-analysis to synthesize results. In this way, systematic reviews and meta-analyzes can generate new and fundamental knowledge for decision-making in the clinical and other areas.